The impacts of replacing air bubbles with microspheres for the clarification of algae from low cell-density culture - Ometto, Francesco; Pozza, Carlo; Whitton, Rachel; Smyth, Beatrice; Gonzalez Torres, Andrea; Henderson, Rita K.; Jarvis, Peter; Jefferson, Bruce; Villa, Raffaella (Elsevier, 2014)
Dissolved Air Flotation (DAF) is a well-known coagulation–flotation system applied at large scale for microalgae harvesting. Compared to conventional harvesting technologies DAF allows high cell recovery at lower energy demand. By replacing microbubbles with microspheres, the innovative Ballasted Dissolved Air Flotation (BDAF) technique has been reported to achieve the same algae cell removal efficiency, while saving up to 80% of the energy required for the conventional DAF unit. Using three different algae cultures (Scenedesmus obliquus, Chlorella vulgaris and Arthrospira maxima), the present work investigated the practical, economic and environmental advantages of the BDAF system compared to the DAF system. 99% cells separation was achieved with both systems, nevertheless, the BDAF technology allowed up to 95% coagulant reduction depending on the algae species and the pH conditions adopted. In terms of floc structure and strength, the inclusion of microspheres in the algae floc generated a looser aggregate, showing a more compact structure within single cell alga, than large and filamentous cells. Overall, BDAF appeared to be a more reliable and sustainable harvesting system than DAF, as it allowed equal cells recovery reducing energy inputs, coagulant demand and carbon emissions.
Keywords: Microalgae harvesting; Dissolved air flotation; Ballasted flotation; Floc structure; Carbon footprint